The Influence of Solar Cell Teaching Kit on Student Learning Outcomes on Energy Concepts - Sumarah, Jati; Wulandari, Ajeng Tiara (Global Education Journal, 2025)
Teaching aids are learning media that can make it easier for students to understand material concepts. So far, the media used in learning is limited, especially in energy. This study aimed to determine how much influence the Solar Cell Teaching Kit has on students' learning outcomes on energy concepts. The method used in the study was an experimental class with a pretest-posttest control group design. The results of the test data analysis show that the average value of student learning outcomes in the experimental class reached 73.33, while in the control class, it was 62.5. This conclusion was obtained based on the hypothesis test results through the t-test on posttest data with a sample of 12 and a significance level of 5%. The result is a calculated t value = 5.613 while t table = 1.782. Because the calculated t value exceeds the t table, it can be concluded that the Solar Cell Teaching Kit significantly influences student learning outcomes on energy concepts.